1997
DOI: 10.3141/1581-06
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Volume-to-Capacity Ratios and Accident Rates

Abstract: The general relationships between hourly accident rates and hourly traffic volume/capacity ( v/c) ratios were examined. A 26 km (16 mi) segment of Interstate I-94 in the Detroit area was selected as the study segment. The v/c ratios were calculated from average hourly traffic volume counts collected in 1993 and 1994 from three permanent count stations. Accident rates were derived from hourly distributed number of accidents in the same 2 years. The correlation between v/c values and accident rates follows a gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(81 citation statements)
references
References 1 publication
9
71
1
Order By: Relevance
“…The results for population density would also tend to confirm the finding that more congested areas result in relatively fewer casualties, although this is less likely to occur in areas with higher employment density, which may be equally congested. Some studies that have found more congested roads to be safer (Zhou & Sisiopiku, 1997) and suggests that policies of reducing congestion in urbanized areas may have unanticipated safety consequences (Shefer & Rietveld, 1997).…”
Section: Land Use Variablesmentioning
confidence: 99%
“…The results for population density would also tend to confirm the finding that more congested areas result in relatively fewer casualties, although this is less likely to occur in areas with higher employment density, which may be equally congested. Some studies that have found more congested roads to be safer (Zhou & Sisiopiku, 1997) and suggests that policies of reducing congestion in urbanized areas may have unanticipated safety consequences (Shefer & Rietveld, 1997).…”
Section: Land Use Variablesmentioning
confidence: 99%
“…Zhou and Sisiopiku 18) found that the correlation between v/c ratio and accident rate follows a general U-shape pattern on the freeways of the United States. Chang, et al 19) as well as Hikosaka and Nakamura 20) observed the same tendency on Korean freeways and Japanese expressways, respectively.…”
Section: (4) Accidentsmentioning
confidence: 99%
“…There is strong empirical evidence of functional relationships between crash rates and traffic flow (Aljanahi, et al, 1999, Cedar and Livneh, 1982, Dickerson, Peirson and Vickerman, 2000, Frantzeskakis and Iordanis, 1987, Garber and Gadiraju, 1990, Gwynn, 1967, Hall and Pendleton, 1989, Jansson, 1994, Johansson, 1996, Jones-Lee, 1990, Maher and Summersgill, 1996, Newberry, 1988, O'Reilly, et al, 1994, Sandhu and Al-Kazily, 1996, Shefer and Rietveld, 1997, Stokes and Mutabazi, 1996, Sullivan, 1990, Sullivan and Hsu, 1988, Vickery, 1969, Vitaliano and Held, 1991, and Zhou and Sisiopiku, 1997. Nevertheless, the manner in which safety is improved by smoothing traffic flow is not well understood at this time.…”
Section: Introductionmentioning
confidence: 99%